Persistence of Vision: Hegemony and Counterhegemony in the Everyday (In Factis Pax: Journal of Peace Education and Social Justice, 2008)
Once upon a time an entire population of birds had forgotten how to fly. So they walked everywhere, generation after generation. Every one complained about sore feet and how ong it took to go anywhere. Finally, one bright bird made the suggestion that they bring in an expert for a weekend long conference on flying. They found such an expert and soon the arrangements were made at a beautiful hotel on a mountaintop. The expert arrived and all joined in singing such lovely songs as “We can fly, we can fly.” They sat and went through the motions, flapping their wings to the instructions of the expert. At the end of the conference, they were all led to the hotel terrace and encouraged to follow the expert as he jumped off and flew around and around. First, only the bravest among them followed, but eventually all were encouraged and took the leap of faith. For an hour they all rode the thermals and glided through the air. Some even sang with delight the songs they had learned. Finally, one by one, they landed on the terrace and took their seats for the closing ceremony. Awards were handed out and praise was heaped upon the expert. After saying farewell, all the birds then walked home.